Source country economic development and dynamics of the skill composition of emigration - Roxana Idu (Economies, 2019)
This paper presents an endogenous growth model of migration and technological diffusion with transitional dynamics, which provide explanations for the empirical pattern of the mobility transition. A two-skill group extension of this model offers new hypotheses regarding the skill composition of emigration during the mobility transition. Skill-biased technological change (SBTC), which first occurs in the destination, raises the relative return to high skill migration and thus the high-to-low skill emigration ratio. As SBTC eventually diffuses to the source economy, it also raises the relative return to high skill investment there, and causes a decline in the high-to-low skill emigration ratio. Empirical evidence using bilateral migration data from 31 destinations and 195 origins is shown to support this hypothesis, with the average income of origins, at which the peak high-to-low skill emigration ratio is reached, is estimated at 2000 in 2011 US dollars PPP (adjusted for purchasing power parity). Furthermore, research and development intensity as a measure of SBTC in destinations is shown to be empirically, positively linked to the bilateral high-to-low skill emigration ratio.
Keywords: O15; O41; F22; 330; migration; human capital; skill-biased technological change; endogenous growth